A Formal Framework for Defining Grid Systems - Nemeth, Z.N.; Sunderam, V. (Cluster Computing and the Grid (CCGrid 2002): 2nd IEEE International Symposium, 2002)
Although there have been several attempts to create grid systems, there is no clear definition for grids. In this paper, a formal approach is presented for defining elementary functionalities of grid systems. A comparative analysis with conventional distributed systems shows that there are semantical differences, not just technical ones. The resulting abstract working model for grids can serve as a framework for defining new systems or analyzing existing ones.